HIV Transmission Networks - Rothenberg, Richard (2009)
PURPOSE OF REVIEW: Over the past several years, one segment of the complex field of HIV transmission dynamics —heterosexual networks—has dominated theoretical and empirical investigation. This review provides an overview of recent work on HIV risks and networks, with a focus on recent findings in heterosexual network dynamics. RECENT FINDINGS: Qualitative (ethnographic) assessments have demonstrated the heterogeneity and complexity of heterosexual connections, particular in Africa where tradition, official polygamy, and unofficial multi-person arrangements lead to concurrency of sexual partnerships. A large, quantitative study on Likoma Island, Malawi, demonstrated the considerable, interlocking sexual connections that arise from a high-concurrency sexual setting, even with a low average number of partnerships (low-degree) of long duration. Such settings, as suggested by ethnographic studies, may be common in Africa and, coupled with newer information about transmissibility during acute and early infection, may provide a plausible explanation for endemic transmission and possibly for rapid HIV propagation. SUMMARY: Recognition of high- concurrency, low-degree networks is an important development for understanding HIV transmission dynamics. Their relevance to heterosexual transmission, and possible extension to other epidemiologic settings, reinforces the heterogeneity and complexity of HIV transmission dynamics.